2016
DOI: 10.1038/cddis.2016.189
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenic potential is restored during differentiation in fusion-reprogrammed cancer cells

Abstract: Detailed understanding of the mechanistic steps underlying tumor initiation and malignant progression is critical for insights of potentially novel therapeutic modalities. Cellular reprogramming is an approach of particular interest because it can provide a means to reset the differentiation state of the cancer cells and to revert these cells to a state of non-malignancy. Here, we investigated the relationship between cellular differentiation and malignant progression by the fusion of four independent mouse ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Markers to identify cancer cell fusion and to isolate cancer hybrid cells include resistance to different antibiotics, or the co-expression of two different fluorescent reporter proteins [31,32,73,123,128,129,133,134,137,138,[140][141][142][143][144][145][147][148][149][150][151][152]154,155,158,161,162,164,167,169,[171][172][173][174]178], or the use of hypoxanthine, aminopterin, or thymidine (HAT) medium [125,160,173,175], respectively.…”
Section: Evidence For Cancer Cell Fusion By In Vitro Studiesmentioning
confidence: 99%
“…Markers to identify cancer cell fusion and to isolate cancer hybrid cells include resistance to different antibiotics, or the co-expression of two different fluorescent reporter proteins [31,32,73,123,128,129,133,134,137,138,[140][141][142][143][144][145][147][148][149][150][151][152]154,155,158,161,162,164,167,169,[171][172][173][174]178], or the use of hypoxanthine, aminopterin, or thymidine (HAT) medium [125,160,173,175], respectively.…”
Section: Evidence For Cancer Cell Fusion By In Vitro Studiesmentioning
confidence: 99%
“…This exciting area of research is especially important in cancers with unusual growth patterns [ [2] , [3] ]. The possibility that reprogramming could turn cancerous cells back to a non-cancerous state is sparking a lot of interest [ [4] , [5] ]. It shows how the environment around cells, along with their genetic makeup and changes in gene expression [ 6 ], play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that fusion of embryonic stem cells (ES cells) with somatic cells can initiate reprogramming of somatic cells to pluripotency by acquiring reprogramming factors from the stem cells 1,2 . Consequently, cell fusion-based reprogramming is increasingly being applied toward understanding epigenetic modifications during the initiation of reprogramming or dedifferentiation 3,4 . Conventionally, cell fusion has been achieved using viruses, 5 polyethylene glycol, 6 and various electrical approaches (i.e., electrofusion) 7,8 .…”
Section: Introductionmentioning
confidence: 99%